1957
DOI: 10.1021/ja01580a051
|View full text |Cite
|
Sign up to set email alerts
|

7-Keto Steroids. I. Steroidal 3-Hydroxy-3,5-dien-7-ones

Abstract: Steroidal 3-Hydroxy-3,5-dien-7-onbs 6303 ethanol and benzene was added to incipient crystallization; yield 20 mg., m.p. 128-133°, 109-125°dec. on admixture with starting material, m.p. 130-136°on admixture with authentic IV, Rgltlc identical with that of authentic IV.2-Acetoxymethyl-3,4,5,6-tetra-0-acetyl-l-bromo-l-deoxyn-glucitol (mannitol?) (VI). (a) With Hydrogen Bromide in Acetic Acid.-To a solution of 2 g. of the epoxide acetate II in 3 ml. of acetic acid was added 3 ml. of acetic acid nearly saturated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1959
1959
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Chromic acid, usually formed in the dissolution of chromium trioxide in aqueous acetic acid, is generally not a useful reagent for epoxidation.104,105 Sodium chromate has been found to be effective for the epoxidation of seco-dodecahedrene, which contains a strained and highly reactive double bond.106 Chromium oxide complexes can oxidize allylic alcohols to various epoxy derivatives,107,108 but epoxides are not known to be the major products from nonfunctionalized alkenes. [109][110][111][112] Chromyl acetate is, compared to chromic acid, a better epoxidation reagent, and epoxides are formed in isolable amounts, especially from highly substituted alkenes, but the yields are generally poor.113-117 Chromyl chloride reacts with most alkenes, but complex mixtures of products are often found; stereochemical and deuterium labeling studies have indicated that epoxides are formed in large amounts, but undergo further oxidation. [118][119][120][121] Chromyl nitrate has been found to be the best epoxidation reagent among these chromyl complexes and epoxidizes a variety of alkenes.…”
Section: Nb and Tamentioning
confidence: 99%
“…Chromic acid, usually formed in the dissolution of chromium trioxide in aqueous acetic acid, is generally not a useful reagent for epoxidation.104,105 Sodium chromate has been found to be effective for the epoxidation of seco-dodecahedrene, which contains a strained and highly reactive double bond.106 Chromium oxide complexes can oxidize allylic alcohols to various epoxy derivatives,107,108 but epoxides are not known to be the major products from nonfunctionalized alkenes. [109][110][111][112] Chromyl acetate is, compared to chromic acid, a better epoxidation reagent, and epoxides are formed in isolable amounts, especially from highly substituted alkenes, but the yields are generally poor.113-117 Chromyl chloride reacts with most alkenes, but complex mixtures of products are often found; stereochemical and deuterium labeling studies have indicated that epoxides are formed in large amounts, but undergo further oxidation. [118][119][120][121] Chromyl nitrate has been found to be the best epoxidation reagent among these chromyl complexes and epoxidizes a variety of alkenes.…”
Section: Nb and Tamentioning
confidence: 99%
“…[a]D -1.5"; ir showed no carbonyl absorption; nmr 6 17a-Hydroxy-7-0xa-Scu-pregnane-3,20-dione (loa). Deketalization of 9 (6.68 g) was accomplished by refluxing with 500 ml of 8% H,SO, in 500 ml of dioxane under N, for 2.5 hr.…”
Section: Methodsmentioning
confidence: 99%
“…7-Ketodehydroepiandrosterone has been shown to improve the memory of mice [4] and 3-acetyl-7-oxo-DHEA increases the resting metabolism of persons on calorie restrictive diets [5]. 7-Ketopregnenolone's has shown anti-cortisone properties [6]. 7-Ketocholesterol has shown some regulatory function in the biosynthesis of cholesterol [7].…”
Section: Introductionmentioning
confidence: 99%